Analisis Modal Kerja Terhadap Pendapatan UMKM GARFANSA (Jellozuyu) - Adelia Novia Putri; Aydah Intana Nurulhudda; Nadia Pramesti; Siva Mutia Rhamadan; Susilowati Susilowati (Universitas Tangerang Raya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, however, they continue to face various limitations, particularly in terms of capital. Working capital is a key factor influencing the smooth operation of business activities and the ability of MSMEs to generate income. This study aims to analyze the effect of working capital on the income of MSME GARFANSA (Jellozuyu), which operates in the milk-based jelly beverage sector. This research employs a descriptive case study approach using primary data obtained from the MSME’s financial statements, including income statements, trial balances, and simple financial records. Data analysis is conducted using a qualitative descriptive method by examining working capital conditions, pricing strategies, income levels, and overall financial performance. The results indicate that well-managed working capital supports smooth production processes, appropriate pricing decisions, and the generation of significant income and profit. Furthermore, MSME GARFANSA demonstrates strong profitability and liquidity levels, reflecting a healthy financial condition. Therefore, it can be concluded that working capital plays an important role in increasing the income of MSME GARFANSA (Jellozuyu).